Production of Arbuscular Mycorrhizal Fungi Spores (AMF) Glomus Coronatum and Glomus Claroideum With Ab Mix Nutrition - Yevita Rombe; Husna Husna; Faisal Danu Tuheteru; Asrianti Arif (Asosiasi Mikoriza Indonesia, 2022)
Arbuscular Mycorrhizal Fungi (AMF) is an obligate fungus that has a symbiosis with plant roots and can stimulate plant growth and productivity so that AMF has the potential to be developed as a biological fertilizer. AMF propagation is influenced by many factors including fertilization. This study aims to determine the effect of giving AB mix nutritional doses on the production of AMF types of Glomus coronatum and Glomus claroideum. The research was conducted at the Plastic House of the Indonesian Mycorrhizal Association Southeast Sulawesi Branch and the Laboratory of the Department of Forestry, Faculty of Forestry and Environmental Sciences, UHO in September - December 2022 using a factorial Completely Randomized Design (CRD) with two factors, namely the first factor was AMF type including Glomus coronatum and Glomus claroideum and the second factor is AB mix nutrition including control, 2.5 ml/1000 ml water, 5 ml/1000 ml water. The results showed that the interaction treatment of AMF Glomus claroideum and the provision of 2.5 ml AB ​​mix nutrition increased the number of AMF spores by 35 spores/5 g zeolite and root colonization by 69.16%.